Postoperative regional anaesthesia and analgesia - Chrubasik, Sigrun; Chrubasik, Joachim (Current opinion in anaesthesiology, 1995)
Regional analgesia is being used with more confidence as a result of better appreciation of the risks and how to avoid them. Refinements to epidural opioid anaesthesia continue to be explored, including the use of continuous infusions rather than intermittent injections, and patient-controlled anaesthesia instead of nurse-adjusted dosing. Is there an optimal dose of an optimal opioid for epidural use and how much can the dose of opioid be reduced? What influence does the site of the catheter tip or use of adjuvants, such as local anaesthetics or α2-adrenergic agents have on the required dose and effectiveness of the opioid? Intrapleural, paravertebral, intercostal, and other nerve blocks remain the province of the enthusiastic expert, but have demonstrable uses. The effectiveness of pre-emptive analgesia continues to be explored, so far with inconsistent effects that are still poorly explained, as does intra-articular analgesia with opioids. If acute pain services are to attract the funding they need, they must justify it in terms of shorter hospital stay. The inclusion of regional techniques as part of balanced analgesia with opioids and non-steroidal anti-inflammatory drugs has shown promise if implemented as part of a multimodal approach to optimize general postoperative care, accelerate the return of gastrointestinal function, and hasten the mobilization of the patient
Gesehen am 18.07.2024